Managing Expectations? The Opportunities and Limitations of e-Learning Applications in Conflict Prevention and Peacebuilding Training. Issue 3 (December 2019) - Demarest, Leila; Smith, Róisín
In recent decades, governmental and non-governmental organisations have increased the number and scale of Conflict Prevention and Peacebuilding (CPPB) activities in conflict-affected countries. This development has also led to an increase in personnel in these organisations, posing challenges for staff training. In response, many organisations are looking at e-learning applications to provide cost-effective training at a broad geographical scale. Online courses and "serious games" have in particular received interest in recent years. In this article, we discuss the opportunities and limitations of such applications for CPPB training. We argue that they face challenges in contributing to skills and knowledge development but emphasise nevertheless that these challenges are similar to those faced by current classroom training initiatives. The potential of technology should not be exaggerated, yet digital applications can broaden the scope of participation and professionalization in CPPB activities to a wider range of (non-Western) actors.